1998
DOI: 10.1161/01.cir.98.20.2180
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effects of Hyperinsulinemia and Ischemia on Myocardial GLUT1 and GLUT4 Translocation In Vivo

Abstract: Background-Myocardial ischemia increases glucose uptake through the translocation of GLUT1 and GLUT4 from an intracellular compartment to the sarcolemma. The present study was performed to determine whether hyperinsulinemia causes translocation of myocardial GLUT1 as well as GLUT4 in vivo and whether there are additive effects of insulin and ischemia on GLUT1 and GLUT4 translocation. Methods and Results-Myocardial glucose uptake and transporter distribution were assessed by arteriovenous measurements, cell fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
1
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 24 publications
2
33
1
3
Order By: Relevance
“…7,24,28 This is supported by the observation that there is an additive effect of AMPK activation or ischemia to insulin-stimulated glucose uptake. 7,28,29 In the present study, however, glucose uptake during insulin stimulation was similar for hearts with low AMPK activity (control) and hearts with high AMPK activity (LVH). This may result from decreased total GLUT4 content in LVH, which limits the capacity for GLUT4-mediated glucose transport.…”
Section: Ampk and Glucose Uptakecontrasting
confidence: 51%
“…7,24,28 This is supported by the observation that there is an additive effect of AMPK activation or ischemia to insulin-stimulated glucose uptake. 7,28,29 In the present study, however, glucose uptake during insulin stimulation was similar for hearts with low AMPK activity (control) and hearts with high AMPK activity (LVH). This may result from decreased total GLUT4 content in LVH, which limits the capacity for GLUT4-mediated glucose transport.…”
Section: Ampk and Glucose Uptakecontrasting
confidence: 51%
“…This contrasts with adipose tissue and skeletal muscle, in which GLUT4 is the major mediator of basal glucose uptake (17)(18)(19). Insulin induces translocation of the GLUT1 transporter in the heart in vivo (13,52), in primary rat adipocytes (17), and in 3T3L1 adipocytes (53). GLUT1 also translocates to the plasma membrane in the heart in response to ischemia (14).…”
Section: Discussionmentioning
confidence: 99%
“…Brosius et al [43] did not find that ischemia in the presence of insulin resulted in additional GLUT-4 translocation. However, when hyperinsulinemia was present, Russell et al [44] reported an increase in GLUT-4 as well as GLUT-1 translocation rate. If indeed alternate pathways regulate ischemia-induced GLUT-4 regulation as effectively as insulin-mediated GLUT-4 activation, then we could show in this study that in hypertrophied hearts not only insulin-regulated glucose uptake is impaired but ischemia as additional stimulus for GLUT-4 translocation did not ameliorate this effect.…”
mentioning
confidence: 99%